EPIDEMIC SITUATION AND TREATMENT PROSPECTS OF MULTIPLE RESISTANT TUBERCULOSIS IN KANTY-MANSIYSKY AUTONOMOUS REGION - E. S. Ershovа; M. V. Pаvlovа; A. V. Vlаdimirov; E. A. Revyakin (Туберкулез и болезни лёгких)
The article describes the changes in the main tuberculosis rates in Khanty-Mansiysky Autonomous Region for the last 10 years. The main areas requiring major efforts and bottlenecks in tuberculosis control are highlighted, and the results achieved in the treatment of multiple drug resistant tuberculosis in this Russian region are presented. The article presents preliminary analysis of treatment efficiency of multiple drug resistant tuberculosis and changes in the epidemics of this most dangerous form of the disease given the introduction and active use of a new generation of anti-tuberculosis drugs.